Foliar Application of Boron and Zinc can Alter Growth and Yield of Gladiolus (Journal of the Bangladesh Agricultural University, 2025)
An experiment was carried out at the Horticulture Farm, Bangladesh Agricultural University, Mymensingh during the period from October 2018 to March 2019 with the objective to investigate the effects of foliar application of boron and zinc on the growth and yield of gladiolus. The experiment consisted of two factors, Factor A: four levels of boron (0ppm, 100 ppm, 200 ppm, 300 ppm) and Factor B: four levels of zinc (0ppm, 100 ppm, 200 ppm, 300 ppm) which was laid out in Randomized Complete Block Design with three replications. The spraying was done at 25 days after sowing (DAS) and 45 DAS. At 60 DAS the 200-ppm concentration of boron showed best performance for plant height (98.33 cm) and number of leaves per plant (6.06), minimum days (62.12 and 72.12 days) required to 80% spike initiation and harvest, maximum spike length (89.17cm), number of spikelets per spike (12.85), yield of corm (14.87 t/ha) and cormel (18.06 t/ha) were recorded from 200 ppm concentration of boron.  On the other hand, 200 ppm zinc was found to be the best for plant height (94 cm) and number of leaves per plant (5.45) at 60 DAS. Minimum days required for 80% initiation of spike (66.14 days) and 80% harvest of spike (77.43), maximum length of spike (85.66 cm), maximum number of spikelets per spike (12.16) was also observed when 200 ppm zinc was used.  Considering the combined effect 200 ppm of boron and zinc was found to be best for plant height (108.60 cm) and number of leaves (8.01) at 60 DAS, and the other parameters. The maximum number of spike (183300/ha), yield of corm (15.51 t/ha) and cormel (23.08 t/ha) was recorded for 200 ppm of boron and 200 ppm of zinc. Considering the above findings, it was clear that the combination of 200 ppm of boron and zinc as foliar application was suitable for better growth, and yield contributing characters of gladiolus.J Bangladesh Agril Univ 23(4): 484–490, 2025